Morbidity and mortality in small for gestational age very preterm infants in a middle-income country - Mangiza, Marcia; Ehret, Danielle E. Y.; Edwards, Erika M.; Rhoda, Natasha; Tooke, Lloyd (Frontiers in Pediatrics, 2022)
Objectives: To evaluate the impact of small for gestational age on outcomes of very preterm infants at Groote Schuur hospital , Cape Town , South Africa.. Study design : Data was obtained from Vermont Oxford Network Groote Schuur database from 2012 to 2018. The study is a secondary analysis of prospectively collected observational data. Fenton growth charts were used to define small for gestational age as birth weight < 10th centile for gestational age. Results : Mortality (28.9% vs 18.5% , adjusted risk ratio (aRR) 2.1, 95% confidence interval CI 1.6-2.7) ,bronchopulmonary dysplasia (14% vs 4.5% , aRR 3.7, 95% CI 2.3-6.1) and late onset sepsis (16.7% vs 9.6%, aRR 2.3, 95% CI 1.6-3.3) were higher in the small for gestational age than in the non-small for gestational age group. Conclusion: Small for gestational age infants have a higher risk of mortality and morbidity among very preterm infants at Groote Schuur Hospital. This may be useful for counselling and perinatal management.